FRI0174 A population based cohort study of rheumatoid arthritis-associated interstitial lung disease: comorbidity and mortality. (15th June 2017) - Hyldgaard, C; Hilberg, O; Pedersen, AB; Ulrichsen, SP; Løkke, A; Bendstrup, E; Ellingsen, T
Abstract : Background: Interstitial lung disease (ILD) is an important reason for excess mortality among patients with rheumatoid arthritis. Objectives: The aim of this study was to compare mortality risks in patients with rheumatoid arthritis-associated interstitial lung disease (RA-ILD) and patients with RA without ILD. Methods: The study was conducted in Denmark, using nationwide, prospectively collected data from the national medical registries. Among patients with RA, diagnosed between 2004 and 2016, 679 patients with RA-ILD were matched for age, gender, and age at RA diagnosis with 11, 722 patients with RA but without ILD. Mortality risks were assessed using Kaplan-Meier survival curves, and hazard rate ratios (HRR) for death were estimated using Cox proportional hazards regression models. Results: The number of prevalent RA patients more than doubled from 15, 352 to 35, 362 individuals during the study period. RA-ILD was seen in 2.2% of incident RA patients. 34.0% of RA-ILD cases were diagnosed within one year prior to and one year after the RA diagnosis. One-year mortality was 13.9% in RA-ILD and 3.8% in non-ILD RA, three-year mortality was 28.0% and 10.9%, and five-year mortality was 39.0% and 18.2%, respectively. The HRRs for death were two to 10 times increased for RA-ILD compared with non-ILD RA, irrespective of follow-up period. Stratified analysis showed that the HRR for death was highest in the first months after the diagnosis of RA-ILD was made, especially in patients diagnosed with RA before diagnosis of ILD. HRR was higher in males and in patients without comorbidity as assessed by the Charlson Comorbidity Index. Conclusions: ILD is a serious complication in RA with a significantly increased mortality compared with a large matched cohort of RA comparisons without ILD. Disclosure of Interest: None declared